Ontology approach for supporting context-aware B2B collaborations - Ang, Chin Teck (2009)
Partner selection is a process that plays a pivotal role in the success of short-term B2B collaborations. A context-aware approach for partner selection was proposed and implemented as a XML-based system that selects and ranks potential partners based on a set of criteria.